2016
DOI: 10.1007/s00294-016-0656-5
|View full text |Cite
|
Sign up to set email alerts
|

CodY, a master integrator of metabolism and virulence in Gram-positive bacteria

Abstract: A growing body of evidence points to CodY, a global regulator in Gram-positive bacteria, as a critical link between microbial physiology and pathogenesis in diverse environments. Recent studies uncovering graded regulation of CodY gene targets reflect the true nature of this transcription factor controlled by ligands and reveal nutrient availability as a potentially critical factor in modulating pathogenesis. This review will serve to update the status of the field and raise new questions to be answered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 113 publications
0
49
0
Order By: Relevance
“…notype for the codY-null mutants has also been reported for B. subtilis, Bacillus thuringiensis, and C. difficile (22)(23)(24)33). Interestingly, while disruption of the codY gene increased the level of sporulation in two strains of C. difficile, significant differences in the sporulation frequencies of those two codY-null mutants were noted; i.e., a codY-null mutant of a poorly sporulating strain exhibited a 2-fold increase in sporulation compared to that for its wild-type parent, while a codY-null mutant of a strongly sporulating strain exhibited 1,400-fold more sporulation than its wild-type parent (23).…”
Section: Figmentioning
confidence: 58%
“…notype for the codY-null mutants has also been reported for B. subtilis, Bacillus thuringiensis, and C. difficile (22)(23)(24)33). Interestingly, while disruption of the codY gene increased the level of sporulation in two strains of C. difficile, significant differences in the sporulation frequencies of those two codY-null mutants were noted; i.e., a codY-null mutant of a poorly sporulating strain exhibited a 2-fold increase in sporulation compared to that for its wild-type parent, while a codY-null mutant of a strongly sporulating strain exhibited 1,400-fold more sporulation than its wild-type parent (23).…”
Section: Figmentioning
confidence: 58%
“…This approach, applied to the CodY regulator, involves mutating the effector binding site to mimic graded nutrient depletion, resulting in protein variants with fixed activation states along the full spectrum of CodY activity. Readers are directed to a recent review by Brinsmade (6) for a detailed summary of these studies. Comparison of the transcriptomes of cells bearing each protein variant has revealed that CodY-regulated genes are expressed as a hierarchy, whereby some target genes are derepressed upon a slight reduction of CodY activity, whereas other target genes remain repressed under the same conditions and are derepressed only upon a more significant reduction of CodY activity (35).…”
Section: Bacterial Adaptation To Nutrient Availabilitymentioning
confidence: 99%
“…pneumoniae (32), and Streptococcus pyogenes (45, 6163). The role of CodY as a regulator of metabolism and virulence has been comprehensively reviewed elsewhere; thus, readers are directed to several recent reviews for more information (6, 24, 64, 65). …”
Section: Bcaas As Indicators Of Cellular Metabolic Statusmentioning
confidence: 99%
“…For instance, the branched-chain amino acid (BCAA) isoleucine seemed to be preferentially synthesized de novo by S. suis in CSF but not in blood. BCAA biosynthesis is a tightly transcriptionally regulated metabolic pathway in bacteria [14]. This prompted us to analyze the transcriptomic adaptation of S. suis in more detail.…”
Section: Introductionmentioning
confidence: 99%